(untitled) (ModaPalavra e-periódico, 2024)
Although it is a phenomenon rich in connections with different aspects of society, fashion is mostly covered in the media and by content creators through topics related to trends, products, celebrities and events in the area. In an era where technology allows the generation of content on a massive scale, where is the voice of these communicators? Would critical content be a way to strengthen discourse and provide greater originality for these communicators? Taking Instagram as a platform, we seek to understand how the discussion about fashion has been updated through the speeches of influencers. Through netnography (Kozinets, 2014) combined with content analysis (Bardin, 2016) based on Verena Figueiredo’s profile, we sought to investigate how the influencer inserts critical content through videos shared on Instagram and how the public responds to it. Our results identified a critical discussion of fashion that is divided into a more specialized one, focused on more specific themes, and a more comprehensive one that uses different themes to deal with large-scale phenomena in the fashion industry. The data points to greater public identification with this broader critical discussion and allows us to infer that influencers can be vectors for a fashion discourse that is not only more questioning, but also more coherent with the changes we have experienced in society as a whole and in the fashion industry.